POSITIVE PERSPECTIVES MATTER: ENHANCING POSITIVE ORGANIZATIONAL BEHAVIOR - Abou Assali, Mouna; Al Dowaikat, Mohammed (PEOPLE: International Journal of Social Sciences, 2021)
This paper is an attempt to shed light on positive organizational behavior and the significance of three psychological perspectives in fulfilling positivity in the workplace, namely the attribution theory of motivation and emotion, the Broaden-and-Build theory, and the emotional intelligence theory. The paper is based on the assumption that these three theories help individuals understand the causes and reactions of other human behavior. In organizations, the way people perceive daily responses or interactions affects everyone’s judgments and actions. Awareness of self-emotions and appropriate attributions of others’ reactions would enhance positive behavior within organizations. Reference to the most relevant literature review is discussed and linked to these three theories as well as the positive impact they create when interrelated with cultural awareness. The main points in each theory are highlighted, followed by a claim that justifies their possible effectiveness in contributing to positive organizational and employee behavior. According to this paper, organizing workshops within the work environment that address positivity theories and their impact on positive behavior will help bridge the gap between individual and organizational cultural values, increase self-awareness and understanding, and boost togetherness, collaboration, and positive attitudes toward others.